An evaluation of internal defects and their effect on trunk surface temperature in Casuarina equisetifolia L. (Casuarinaceae) - Leong, Eng-Choon (2015)
Tree risk assessment is important when communities choose to cultivate trees near people and property, and many tools may be used to enhance these assessments. The effectiveness of determining internal tree stem condition by measuring trunk surface temperatures with infrared cameras was assessed in this study. The trunk surface temperature of 48 Casuarina equisetifolia was evaluated; the trees were felled and dissected to quantify internal stem defects; and a mixed-methods approach was employed to determine the presence of defects. In total, 27% of trees were decayed, 62% discolored, 6% cavitated by termite infestations, and 2% undamaged. Qualitative visual evaluation of the infrared images revealed the close association of external stem features, opposed to internal defects, with surface temperature distributions. External features, such as cankers, detached bark, and mechanical damage, were associated with temperature anomalies. The trees’ internal condition accounted for a small percentage of the variability in evaluated temperature measurements (r2 = 0.001-0.096). Overall, no clear relationship was found between the extent of internal defects and surface temperature distributions. These results are practically important for the arboricultural professional community because they show the technique does not provide accurate results about the internal condition of trees.